Astrocyte pathology in the ventral prefrontal white matter in depression - Rajkowska, Grazyna; Legutko, Beata; Moulana, Mohadetheh; Syed, Maryam; Romero, Damian G.; Stockmeier, Craig A.; Miguel-Hidalgo, Jose Javier (Journal of psychiatric research, 2018)
Astrocyte functions in white matter are less well understood than in gray matter. Our recent study of white matter in ventral prefrontal cortex (vPFC) revealed alterations in expression of myelin-related genes in major depressive disorder (MDD). Since white matter astrocytes maintain myelin, we hypothesized that morphometry of these cells will be altered in MDD in the same prefrontal white matter region in which myelin-related genes are altered. White matter adjacent to vPFC was examined in 25 MDD and 21 control subjects. Density and size of GFAP-immunoreactive (-ir) astrocyte cell bodies was measured. The area fraction of GFAP-ir astrocytes (cell bodies + processes) was also estimated. GFAP mRNA expression was determined using qRT-PCR. The density of GFAP-ir astrocytes was also measured in vPFC white matter of rats subjected to chronic unpredictable stress (CUS) and control animals. Fibrous and smooth GFAP-ir astrocytes were distinguished in human white matter. The density of both types of astrocytes was significantly decreased in MDD. Area fraction of GFAP immunoreactivity was significantly decreased in MDD, but mean soma size remained unchanged. Expression of GFAP mRNA was significantly decreased in MDD. In CUS rats there was a significant decrease in astrocyte density in prefrontal white matter. The decrease in density and area fraction of white matter astrocytes and GFAP mRNA in MDD may be linked to myelin pathology previously noted in these subjects. Astrocyte pathology may contribute to axon disturbances in axon integrity reported by neuroimaging studies in MDD and interfere with signal conduction in the white matter.